2005
DOI: 10.1158/0008-5472.can-05-2240
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Serous Low Malignant Potential, Low-Grade, and High-Grade Tumors of the Ovary

Abstract: Papillary serous low malignant potential (LMP) tumors are characterized by malignant features and metastatic potential yet display a benign clinical course. The role of LMP tumors in the development of invasive epithelial cancer of the ovary is not clearly defined. The aim of this study is to determine the relationships among LMP tumors and invasive ovarian cancers and identify genes contributing to their phenotypes. Affymetrix U133 Plus 2.0 microarrays (Santa Clara, CA) were used to interrogate 80 microdissec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
221
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 291 publications
(247 citation statements)
references
References 47 publications
23
221
0
3
Order By: Relevance
“…However, the very substantial differences in gene expression between serous LMP and invasive tumors, observed in this study and others (8)(9)(10), confound such analyses. The identification of LLI tumors created the opportunity to examine gene expression differences between tumors that are very similar molecularly but differ phenotypically in terms of their invasiveness.…”
Section: Identification Of Lmp-like Invasive Tumorsmentioning
confidence: 62%
See 3 more Smart Citations
“…However, the very substantial differences in gene expression between serous LMP and invasive tumors, observed in this study and others (8)(9)(10), confound such analyses. The identification of LLI tumors created the opportunity to examine gene expression differences between tumors that are very similar molecularly but differ phenotypically in terms of their invasiveness.…”
Section: Identification Of Lmp-like Invasive Tumorsmentioning
confidence: 62%
“…S2; GSEA analysis in Supplementary Table S3). To verify that the enrichment and overexpression of RAS-MAPK-related transcripts were, in fact, up-regulation in LMP tumors rather than a loss of these genes in invasive carcinomas, we compared our LMP dataset to normal ovarian surface epithelium data from Bonome et al (8). We found that RAS-MAPK pathway genes (enriched gene lists derived from Panther, DAVID, and GSEA) were highly overrepresented among genes that were overexpressed (2-fold greater expression, q < 0.05) in serous LMP compared with ovarian surface epithelium, with a statistical significance of P < 2.2eÀ16 (Fisher exact; see also Supplementary Fig.…”
Section: Comparison Of Expression Profiles Between Lmp and Invasivementioning
confidence: 99%
See 2 more Smart Citations
“…As previously described, it utilizes two cycles of complementary DNA (cDNA) synthesis and in vitro transcription for the amplification of 50-100 ng of total RNA (Bonome et al, 2000). Labeled amplified RNA was then hybridized to the Affymetrix Human Genome U133 Plus 2.0 GeneChip (Affymetrix, Santa Clara, CA, USA), which contains over 55 000 probe sets representing more than 47 000 transcripts derived from well characterized genes.…”
Section: Tissue Samplesmentioning
confidence: 99%